Forensic autopsies of geriatric deaths conducted in elazig - Turkoglu, Abdurrahim; Tokdemir, Mehmet; Bork, Turgay; Tuncez, Ferhat Turgut (Geriatrics Society, 2014)
Introduction: The elderly population is rapidly growing throughout the world due to the increased life span of individuals, parallel to advances in the fields of medicine and technology, improvements in socio-economic conditions, and a decreased reproduction rate. The aim of the present study was to get epidemiological data on forensic deaths and autopsy findings in elderly people.; Materials and Method: Of 1439 cases that underwent an autopsy in the Department of Forensic Medicine in Elaz›g Firat University Faculty of Medicine in a five-year period between January 2008 and December 2012, 345 cases (23.9%) aged 65 and over were evaluated for age, gender, and place and cause of death.; Results: The mean age of the cases was 73.7±7.6 years; 24 (73.6%) were males and 91 (26.4%) were females. Of these deaths, 207 (60.0%) occurred in the city center. Accidents were the most common cause of death, occurring in 181 cases (52.5%), followed by natural causes occurring in 112 (32.5%) cases. Traffic accidents (54.3%) and falls (21.5%) were found to be the most common causes of unnatural death, and myocardial infarction (72.1%) and cerebrovascular diseases (11.5%) was the most common causes of death from natural causes. 63% (80 cases) of traffic accidents were pedestrian accident.; Conclusion: In order to reduce mortality in the elderly population, more emphasis must be placed on personal health checks, which should be performed with higher frequency. More stringent safety measures should be taken in order to reduce the risk of accidents, and public awareness should be raised regarding the safety of elderly people. © 2014, Geriatrics Society. All rights reserved.
Elaziğ’da adli otopsisi yapilan geriatrik Ölümlerin değerlendirilmesi
Keywords: Aged; Autopsy; Death; Forensic Medicine